Integrated Environmental Accounting for Assessing the Value for Money in Marine Protected Areas: the Case of Tremiti Islands (Italy) - Visintin, Francesca; Tomasinsig, Elisa; Spoto, Maurizio; Marangon, Francesco; Mastrototaro, Francesco; Chimienti, Giovanni; Montesanto, Federica; Troiano, Stefania (Journal of Environmental Accounting and Management, 2026)
The paper focuses on the integrated environmental accounting model called ``eValue’’ developed for protected areas and applied in the research programme coordinated by the Italian Ministry of Environment aiming to implement an environmental accounting system for the Italian Marine Protected Areas (MPAs). eValue aimed to calculate the economic value of Protected Areas adopting a Cost-Benefit Analysis approach. Financial accounting based on costs and revenues was integrated with environmental accounting, which reflected not only environmental costs but also environmental revenues, i.e. environmental benefits. Environmental costs assessed the impacts related to human activities in the MPA and environmental benefits assessed ecosystem services. The overall annual flow account accounted for costs and benefits, both economic and environmental, and the difference represented the value produced (or consumed) by the MPA. The eValue model was applied in the Tremiti Islands MPA. eValue demonstrated that the annual benefits-costs ratio reaches 2.1. In addition, the ratio between the net benefit and the public funding is 5.0 completely covering the amount of public transfers and thus summarizing the overall value for money of the MPA. Finally, the outcomes of the project are functional to the Mapping and Assessment of Ecosystem Services initiative carried out by the European Union.